Project management in manufacturing enterprises - Vrchota, Jaroslav; Řehoř, Petr (Serbian Journal of Management, 2021)
Current time of turbulent changes is related to the necessity of innovation, of both the products and the entire organization management system. However, innovation activities must be implemented in a short time. Unfortunately, most of the organizations struggle with insufficient costs and the lack of creative and active human resources. All of this might lead to a loss of market position and a decrease in competitiveness. If an organization wants to succeed on the market and survive in the long term, the trial and error method is ruled out. The project management is a possible way of dealing with the issue. Project management is characterized by a detailed examination of all the aspects of the project, their detailed planning, culminating in the implementation of the change and innovation. Therefore, the current managers need to define the precise goals, the responsible persons, and deadlines, allocate the tasks, costs and define the procedures crucial for project management clearly. Only in this way an organization is able to react to major changes quickly and without any mistakes. The aim of the paper is to evaluate the factors, important for the manufacturing enterprises in the projects, and to find out the relations of such factors. The research was carried out in 2019 in 116 manufacturing enterprises in the Czech Republic. The project managers often focus their attention on customer satisfaction and cost magnitude in evaluating of the projects.